Henry's clinical diagnosis and management by laboratory methods. - 4 0 16; 1928- McPherson, Richard A.;Pincus, Matthew R.;Henry, John Bernard; 5 ([Philadelphia, Pa.] : Saunders Elsevier, 2007)
A comprehensive guide on clinical pathology and laboratory medicine, detailing information on the purposes, practices, and management of the clinical laboratory; laboratory evaluations; the basic examination of urine, blood, and bone marrow; advancements in thromboembolic phenomena; immunology; medical microbiology; clinical and molecular pathology; and methods for early detection.
Rev. ed. of: Clinical diagnosis and management by laboratory methods / [edited by] John Bernard Henry. 20th ed. c2001.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Diagnosis, Laboratory.;Clinical Laboratory Techniques.;Diagnosis.;Pathology.; 20; 2